2020
DOI: 10.47993/gmb.v43i1.13
|View full text |Cite
|
Sign up to set email alerts
|

El tratamiento intralesional de Leishmaniasis cutánea es seguro frente al riesgo de complicaciones mucosas?

Abstract: Objetivo: evaluar la seguridad a largo plazo frente al riesgo de complicaciones mucosas del uso intralesional de antimoniales pentavalentes en pacientes con Leishmaniasis cutánea comparado con el uso sistémico de los mismos. Métodos: estudio observacional, cuantitativo de tipo longitudinal retrospectivo. Se analizó un total de 66 registros clínicos de pacientes, con diagnóstico de Leishmaniasis cutánea del parque Isiboro Secure durante el periodo 2012 a 2016. Se evaluó un total de 46 tratamientos sistémi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…In the context of Latin America, ninety-two patients were treated through intralesional route with an antimonial lidocaine- MA compound with good effectiveness and a low number of side effects [ 40 ], however, we argue that it is more advantageous to use the standard drug with no anesthetic, due to lesser risk of contamination of the standard drug. IL MA was described as a safe and effective option treatment for CL in a Bolivian rainforest rural area [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of Latin America, ninety-two patients were treated through intralesional route with an antimonial lidocaine- MA compound with good effectiveness and a low number of side effects [ 40 ], however, we argue that it is more advantageous to use the standard drug with no anesthetic, due to lesser risk of contamination of the standard drug. IL MA was described as a safe and effective option treatment for CL in a Bolivian rainforest rural area [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL MA has been widely used in other states and countries in Latin America with proven efficacy [7,11,20,21,22,27,40,41]. A multicenter clinical trial with IL MA is being concluded in Brazil with the coordination of our reference center.…”
Section: Discussionmentioning
confidence: 99%
“…Se calcula que cada año hay en el mundo entre 600 000 y 1 millón de nuevos casos (4). Los antimoniales pentavalentes son los medicamentos de primera línea para el tratamiento de la leishmaniasis cutánea y se administran sistémicamente (vía endovenosa o intramuscular) a una dosis de 20 mg/kg/día por 20 días (5). Frente a las limitaciones expuestas se han explorado otros medicamentos, con un uso menos frecuente; entre estos, los más estudiados son fármacos antifúngicos tales como los azoles (ketoconazol, fluconazol, itraconazol).…”
Section: Introductionunclassified